Handbook of Tuberculosis - Grosset, Jacques H.; Chaisson, Richard E. (Springer International Publishing : Imprint: Adis, 2017)
This concise, clinically focused handbook offers a complete overview of tuberculosis and reviews the latest guidelines, treatment options, clinical trials and management of this disease. Handbook of Tuberculosis is a well-rounded book written by renowned researchers at the Johns Hopkins Center for Tuberculosis Research. The easily accessible text offers infectious disease specialists, pulmonologists, and other healthcare workers an excellent quick reference tool, with full color tables and figures enhancing the text further. Tuberculosis is a life-threatening lung infection that affects people of all ages. It is the second biggest cause of death from infectious diseases and is the most common cause of death amongst patients with HIV/AIDS. Education on the recognition of tuberculosis and the subsequent treatment of the disease is empirical to the prevention of wide-spread resistance. There is a lack of knowledge on how to treat coinfected and comorbid patients, this handbook offers the latest medical guidance and treatment options to equip physicians to manage such patients.